2018
DOI: 10.1364/ol.43.001319
|View full text |Cite
|
Sign up to set email alerts
|

Compact high-efficiency vortex beam emitter based on a silicon photonics micro-ring

Abstract: Photonic integrated devices that emit vortex beam carrying orbital angular momentum are becoming key components for multiple applications. Here we propose and demonstrate a high-efficiency vortex beam emitter based on a silicon micro-ring resonator integrated with a metal mirror. Such a compact emitter is capable of generating vortex beams with a high efficiency and small divergence angle. Vector vortex beams of various topological charges are selectively generated by the emitter at different wavelengths with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The angle θ dictates the magnitude of the topological charge. The great advantage of such devices is their ultra-compact size and extremely simple operation [164,165], which make them easy to integrate with other on-chip components, such as modulators and lasers, to form photonic integrated circuits, enabling large-scale integrated photonic applications.…”
Section: On-chip Optical Vortexmentioning
confidence: 99%
“…The angle θ dictates the magnitude of the topological charge. The great advantage of such devices is their ultra-compact size and extremely simple operation [164,165], which make them easy to integrate with other on-chip components, such as modulators and lasers, to form photonic integrated circuits, enabling large-scale integrated photonic applications.…”
Section: On-chip Optical Vortexmentioning
confidence: 99%
“…Some of the resonances were far from the critical coupling condition and then most of the optical power transmitted through the access waveguide, which lead to inefficient emission. The efficiencies can be improved by engineering optimized coupler for the ring and integrating a mirror below the angular grating to reduce down emitting loss [25]. It is observed that the resonances of TE 0 and TE 1 WGMs coincide at two wavelengths of 1 c λ (1550 nm) and 2 c λ (1622 nm), thus OAM multiplexing can be implemented at both wavelengths.…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…The spatial-frequency loss through the two lens results the primary mode mismatch between the incident beam and the near-field mode of the DEMUX. Optimized experiment should use high-efficiency device with a bottom mirror to generate concentrated beam [25], and lens with high NA and large aperture to collect complete emission and suppress the diffraction of the propagating beam. The 3-dB bandwidth for channels of 1,2 p  is 9 GHz, and for channels 3,4 p  the bandwidth is 40 GHz.…”
Section: Chip-to-chip Transmissionmentioning
confidence: 99%
“…In this paper, we experimentally demonstrate a FMF link based on a micro-meter-sized highly efficient silicon integrated optical vortex beam emitter. The device is capable of emitting vector optical vortices carrying well-defined OAM efficiently with the efficiency of the device >37% [39,40]. Using this device, seven modes, each modulated by 20-Gbit/s quadrature phase-shift keying (QPSK) signal have been successfully transmitted through 2-km two-mode FMF (LP 01 and LP 11 ) and 3.6-km three-mode FMF (LP 01 , LP 11 and LP 21 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1(b). An aluminum mirror is introduced below the micro-ring resonator by wafer bonding technology to the structure to effectively improve the emission efficiency [39,40].…”
Section: Introductionmentioning
confidence: 99%